Sustainable Supply Chain Management: A Comparative Analysis of Green Practices in Manufacturing Industries - Boro, Bijay Chandra; Kumar, Alok; Saxena, Kokila (Journal of Neonatal Surgery, 2025)
This study examines sustainable supply chain management (SSCM) through a comparative analysis of green practices in the automotive, electronics, and textile industries, focusing on Toyota, Samsung, and H&M. Despite growing environmental pressures, cross-industry comparisons of SSCM practices remain limited. This research addresses this gap by evaluating the adoption and effectiveness of green practices across procurement, production, and logistics, guided by the triple bottom line (TBL) and stakeholder theory. A qualitative comparative case study approach is employed, using secondary data from sustainability reports, Scopus-indexed journals, and industry analyses. Findings reveal that all three industries adopt sustainable sourcing, energy-efficient production, and low-emission logistics, achieving 12-30% CO2 reductions. However, the automotive industry leads with lean-green integration, electronics emphasizes eco-design, and textiles prioritizes water efficiency. Common challenges include high costs and supply chain complexity, while best practices involve supplier collaboration, technology integration, and circular economy principles. The study proposes a cross-industry SSCM framework to facilitate learning and adoption. Theoretical contributions include enriching TBL and stakeholder theory applications, while practical implications guide managers in optimizing green practices. Policy recommendations advocate for stronger regulations and incentives. Despite limitations in secondary data reliance, this study advances SSCM scholarship and practice, aligning with Sustainable Development Goal 12.